2015
DOI: 10.1165/rcmb.2014-0163oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Hypertension in Rats Due to Age-Related Arginase Activation in Intermittent Hypoxia

Abstract: Pulmonary arterial hypertension (PAH) is prevalent in patients with obstructive sleep apnea syndrome (OSAS). Aging induces arginase activation and reduces nitric oxide (NO) production in the arteries. Intermittent hypoxia (IH), conferred by cycles of brief hypoxia and normoxia, contributes to OSAS pathogenesis. Here, we studied the role of arginase and aging in the pathogenesis of PAH in adult (9-mo-old) and young (2-mo-old) male Sprague-Dawley rats subjected to IH or normoxia for 4 weeks and analyzed them wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…As for any other PH animal model available, it has several limitations and some concerns should be kept in mind when interpreting the results obtained with this model [ 32 , 33 ]. Against the background of the fact that most studies investigating the role of Arg in PH development as well as effects of enzyme inhibition were performed using models of hypoxia induced PH [ 19 , 20 , 28 , 35 ], it is of certain scientific interest to elucidate these processes in the MCT model as performed in the current study. Protein expression and tissue distribution analysis clearly showed an increased expression of both, Arg I and Arg II in induced PH compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for any other PH animal model available, it has several limitations and some concerns should be kept in mind when interpreting the results obtained with this model [ 32 , 33 ]. Against the background of the fact that most studies investigating the role of Arg in PH development as well as effects of enzyme inhibition were performed using models of hypoxia induced PH [ 19 , 20 , 28 , 35 ], it is of certain scientific interest to elucidate these processes in the MCT model as performed in the current study. Protein expression and tissue distribution analysis clearly showed an increased expression of both, Arg I and Arg II in induced PH compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…While for Arg II, a 5.1-fold increase was observable, Arg I revealed a 22.7-fold increase. The finding is novel and its discussion against the background of the available literature is challenging due to most in vivo studies in animal models, predominantly models of hypoxia induced PH, focusing on Arg II, while not comparatively looking for Arg I or even differentiating between the isoforms [ 12 , 18 , 19 , 20 , 21 , 22 , 29 , 36 ]. This might be for the following reasons: first, Arg isoform expression depends on both, the species used for an animal model as well as the pathologic stimulus leading to Arg up-regulation (reviewed in [ 7 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arginase has two isoforms which are encoded by two distinct genes: arginase-1 (ARG1) on chromosome 6 (Sparkes et al 1986) and arginase-2 (ARG2) on chromosome 14 (Gotoh et al 1997). The induction of arginase is involved in many disease states, including asthma (Morris et al 2004;Morris 2012), sickle cell disease (Morris et al 2005;Morris 2012), vascular diseases (White et al 2006;Morris 2012), and PH (Grasemann et al 2015;Nara et al 2015;Steppan et al 2016). We have previously shown that NOS and arginase compete for their common substrate, L-arginine, such that greater expression and/or activity of one results in lower activity of the other due to limitations in L-arginine bioavailability (Nelin et al 2002(Nelin et al , 2007Chicoine et al 2004;Stanley et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They are associated with blockade of arginase II. When this occurs, eNOS is activated, which leads to the correction of endothelial dysfunction (Suwanpradid et al 2014, Rath et al 2014, Pandey et al 2014, Nara et al 2015, Krause et al 2015, Steppan et al 2016.…”
Section: а B D Cmentioning
confidence: 99%